2018
DOI: 10.3389/fmicb.2018.02976
|View full text |Cite|
|
Sign up to set email alerts
|

Bacteroides fragilis Prevents Clostridium difficile Infection in a Mouse Model by Restoring Gut Barrier and Microbiome Regulation

Abstract: Clostridium difficile is currently the leading cause of nosocomial infection. Antibiotics remain the first-line therapy for C. difficile-associated diseases (CDAD), despite the risks of resistance promotion and further gut microbiota perturbation. Notably, the abundance of Bacteroides fragilis was reported to be significantly decreased in CDAD patients. This study aimed to clarify the prophylactic effects of B. fragilis strain ZY-312 in a mouse model of C. difficile infection (CDI). The CDI mouse model was suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 33 publications
3
61
0
1
Order By: Relevance
“…suggesting that the inflammation induced by wild type C. difficile in our mouse model selects against a Bacteroidaceae population expansion. In support of this, negative associations between C. difficile and members of the Bacteroidaceae have been reported in human studies, as well as in vitro, and in mouse models of CDI[59][60][61][62][63] . Further work is necessary to identify which mediator(s) of host inflammation are responsible for the restriction of the Bacteroidaceae in our model of CDI.…”
supporting
confidence: 53%
“…suggesting that the inflammation induced by wild type C. difficile in our mouse model selects against a Bacteroidaceae population expansion. In support of this, negative associations between C. difficile and members of the Bacteroidaceae have been reported in human studies, as well as in vitro, and in mouse models of CDI[59][60][61][62][63] . Further work is necessary to identify which mediator(s) of host inflammation are responsible for the restriction of the Bacteroidaceae in our model of CDI.…”
supporting
confidence: 53%
“…We also recently reported that C. difficile growth on epithelial cells in an in vitro gut model was reduced in the presence of B. doreP 8 . B. fragilis has been recently reported to prevent C. difficile infection in a murine infection model by potentially impacting the integrity of the epithelial barrier 64 . While these data support a role for Bacteroides spp in preventing C. difficile infection, patients infected with C. difficile generally have a reduction in the abundance and diversity of Bacteroidetes 61 .…”
Section: Discussionmentioning
confidence: 99%
“…"+++" indicates the metabolite with the strongest growth-promoting capability, while the "+" means that the metabolite induced a mild growth promotion results in significant perturbation of the gut microbiome, it is conceivable that this model would demonstrate increased susceptibility to infections by other enteric pathogens such as Salmonella enterica serovar Typhimurium, Citrobacter rodentium, and Clostridium difficile. However, for the aforementioned enteric pathogens, there already exists a wellestablished adult mouse model [50,51]. Here, we suggest a simple and convenient animal model to study V. cholerae infection.…”
Section: Discussionmentioning
confidence: 99%